2016
DOI: 10.1186/s11671-016-1305-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-sowing Seed Treatment with Metal Nanoparticles on the Formation of the Defensive Reaction of Wheat Seedlings Infected with the Eyespot Causal Agent

Abstract: The paper presents research data of lipid peroxidation and lectin activity in wheat seedlings at seed treatment with solution of metal nanoparticles (Zn, Ag, Fe, Mn, Cu) and sole solution of copper nanoparticles under the high pathogen infection background of Pseudocercosporella herpotrichoides (Fron) Deighton (synonym: Oculimacula yallundae (Wallwork & Sponer) Crous & W. Gams). It was shown that investigated nonionic colloidal solutions of biogenic metals have the antioxidant effect through the inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
0
22
0
1
Order By: Relevance
“…There is no single opinion on the impact of metal nanoparticles upon physiological and biochemical processes in plants in available literature—as positive and negative effects are noted. Our previous studies have shown change in element metal content in roots and shoots of winter wheat plants at colloidal solution nanosized particles of metal (Cu, Zn, Fe, Mn) action [5, 6]. Also, we got a positive nanomolybdenum impact upon the root microflora Cicer arietinum L. [7].…”
Section: Introductionmentioning
confidence: 83%
“…There is no single opinion on the impact of metal nanoparticles upon physiological and biochemical processes in plants in available literature—as positive and negative effects are noted. Our previous studies have shown change in element metal content in roots and shoots of winter wheat plants at colloidal solution nanosized particles of metal (Cu, Zn, Fe, Mn) action [5, 6]. Also, we got a positive nanomolybdenum impact upon the root microflora Cicer arietinum L. [7].…”
Section: Introductionmentioning
confidence: 83%
“…An increase in the ROS level might induce membrane lipid peroxidation in cells ( Panyuta et al, 2016 ). In order to investigate the effects of SNP and CaCl 2 on the development of adventitious root under osmotic stress, the changes in TBARS in cucumber explants were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore Mn nanoparticles are viewed as a stimulant of plant growth and of metabolic processes as alkaloids production. In infested soils, foliar exposure to Mn oxide nanoparticles reduces disease up to 28% as compared to controls [62], the plants can have cross-tolerance between abiotic and biotic stresses, and in this regard stress tolerance can help plants to form faster and more resistant manner to additional environmental changes. The propose mechanism for the distribution of Mn nanoparticles through the plant incudes transportation from the root through the vascular system, a process considered as active-transporting as long as includes signaling, recycling and plasma membrane regulation.…”
Section: Nanoparticles and Their Action On Plantsmentioning
confidence: 99%